(untitled) (Journal of Human Sciences, 2020)
This research deals with the relationship of pre-Islamic poetry with the spring season. It discusses how the emotions of poets filled within their poems embodied through the relationship of spring with the home of the beloved, where they were dating in this picturesque square, as their poems envisioned. The research deals with the effect of spring on the animal and how the Bedouin benefited from this season in knowing fertility of the season, then how poets will take advantage of this in their expressions. The poet’s fascination with the spring remains in control of his feeling, linking him to the woman he loves so that she also becomes another flower of spring flowers. The artistic pictures of women inside the poems in the color of spring tell the story of harmony and co-ordination between this blooming season and the beauty of women.